Digital Transformation of Tax Administration in the Big Data Era: An Analysis of Organizational Readiness, Cybersecurity, and Education Strategies Based on Global Best Practices - Edi Purwanto (Journal Research of Social Science, Economics, and Management, 2026)
The digitization of tax administration has shifted from simply automating business processes to massive data integration known as Tax Administration 3.0. However, many tax authorities struggle with organizational unpreparedness, cybersecurity vulnerabilities, and low digital literacy among taxpayers. This research aims to analyze digital transformation strategies through three main pillars: organizational readiness, data security, and taxpayer education. Using a systematic literature review method and comparative analysis of best practices in Australia, Estonia, and the United Kingdom, this study synthesized findings from 45 academic articles, policy documents, and international reports published between 2015-2024. The study found that technological success relies heavily on changing organizational culture to data-driven, strengthening inclusive cyber architectures, and personalized educational strategies. The results of the literature synthesis recommend an integrated framework that aligns data protection regulations with the core tax system to ensure voluntary compliance in the digital economy era. This research provides a strategic framework for tax authorities to balance administrative efficiency with taxpayer data protection, ultimately supporting sustainable.